Profiling Brain Trauma in Professional American-style Football and the Implications to Developing Neurological Injury - Karton, Clara (Université d'Ottawa / University of Ottawa, 2019)
American-style football participation is associated with high risks to a spectrum of sports-related brain injury involving acute reactions and chronic manifestations. Traditional methods of identifying injury have proven ineffective at protecting athletes and mitigating risk as they rely on the presence and recognition of inconsistent symptom expression. This is, in part, due to the lack of an objective measure of quantifying exposure. Brain trauma profiling was defined to capture a spectrum of exposure by incorporating the primary characteristics that associate with risk of neurological injury. This profile includes strain magnitude associated with impact, frequency at which impacts are experienced, time interval between impacts, over the duration of exposure. Trauma profiling methods differentiated player field position in professional American-style football where three unique trauma profiles were identified based on similarities among the characteristics of trauma. Regional strain from common head impacts showed that distribution was independent of field position regardless of variation in impact conditions. Rather, brain regions vulnerable to strains were dictated by the frequency and magnitude that govern the position profile. The extent of tissue volume involved in common head impacts was field position dependent. Skill positions tended to experience impacts involving greater tissue volumes reaching deeper white matter structures, but were infrequent. Impacts common to line positions typically involved less brain tissue of predominately superficial cortical gray matter, but were experienced at high frequency counts. The primary findings from this research show that brain trauma profiling may be used as an objective measurement tool to define exposure. The results indicate that exposure is not uniform and that brain trauma and injury risk can be described using unique combinations of these characteristics. Regional areas vulnerable to strain are dictated by the frequency and magnitude of impact and therefore in order to effectively protect against brain injury, both characteristics need to be managed. Lastly, this research demonstrates that either few impacts involving high brain volume or frequent impacts with little brain volume involvement may both result in brain dysfunction. Brain trauma profiling methods has broad application in future research. This measurement tool will be useful in identifying how injury occurs in various sports, military units, and particularly important for vulnerable populations and the developing brain. This knowledge is instrumental in establishing risk prevention strategies and public health policies for specific environments.
Keywords: Brain trauma; Biomechanics; Neurological injury; American-style football; Head impact